Exploring Barriers and Facilitators to Rural Harm Reduction Programs that Target Opioid Use Disorder - Dracup, Erin (My University, 2025)
The purpose of this project is to explore factors that serve as barriers or facilitators to the provision of harm reduction programs in rural areas in North Carolina. North Carolina has been deeply impacted by the opioid epidemic, and opioid-related harm rates exceed national averages in many parts of our state, with rural areas experiencing the highest rates of harm. Harm reduction programs seek to mitigate opioid-related harm by providing services such as naloxone, fentanyl test strips, peer support, safe needles, and treatment referrals. Research indicates people living in rural areas experience higher rates of opioid-related harm, and this project seeks to contribute to understanding how to meet the needs of rural communities through the provision of harm reduction services. This qualitative descriptive study used secondary data from an in-progress parent study titled, “Facilitators and Barriers to Harm Reduction Services.” The parent study includes interviews with harm reduction workers throughout North Carolina. Through analysis of the interviews, person-centered care, advertisement, and community partners were identified as facilitators; funding and education were identified as facilitators or barriers; policy, transportation, and stigma were identified as barriers. These identified barriers and facilitators suggest ways that harm reduction workers, specifically those working in rural areas, can increase the efficacy of their programs. Workers should be conscious of these barriers and facilitators and use them to make well-informed decisions about their program.
Keywords: opioid use disorder; harm reduction; rural settings